Character, Acting and Being on the Pre-modern Stage - Burns, Edward. author. aut Link
IX, 238 p.
Keywords: An analysis of acting and characterization on stage, covering theories of character from Aristotle to Brecht and approaches from formalism to post structuralism. The Early Theatre Group have, over the last 5 years, used an experimental approach to performing some of the plays written about here.